Prawnokarna ocena prób samobójczych - Grudecki, Michał (PRAWO i WIĘŹ, 2024)
The paper is devoted to the criminal assessment of suicide attempts. The author analyzes suicide attempts in terms of whether such behavior fulfills the premises of a crime. He proves that the behavior of a suicide attempt is a criminal act that fulfills the characteristics of the crime of attempted homicide. Due to the intentional violation of the inalienable legal interest, which in the Polish legal system is human life, in a manner contrary to the socially accepted rules of dealing with this interest, the degree of social harmfulness of an attempted suicide will usually exceed the threshold of insignificance. Attempted suicide, however, is not a crime, because at the time of the act, the would-be suicide is not guilty due to the abnormal motivational situation in which he found himself. Nevertheless, his act is unlawful, and therefore people who save a suicide and thus violate his legal interests, act legally, using the justifications of necessary defense. In the author’s opinion, the lack of the right to commit suicide while at the same time violating the criminal protection of life (e.g. necessary defense, permitted abortion or freedom from compulsory treatment) proves the inconsistency of the Polish legal system.